PENGARUH KOMUNIKASI, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS SOSIAL, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN PONOROGO - Suwendi Suwendi; Suwardi Suwardi; Herning Suryo Sardjono (Master of Public Administration, Universitas Slamet Riyadi, 2023)
The purpose of this study was to know the effect of organizational commitment and organizational communication on the performance employees of BUMDes Parringan Madu in Parringan Village, Jenangan District, Ponorogo Regency. This research is a survey research and is classified as explanatory research. This research was conducted at the Parungan Madu BUMDes, Parringan Village, Jenangan District, Ponorogo Regency. The research population employees totaling 34 people and all of them were used as samples. Data collection techniques used questionnaires and literature study. Data analysis technique using multiple linear regression. The results showed that organizational commitment had a positive and significant effect on the performance employees of BUMDes Parringan Madu with a t value of 7.917 with a p value (0.000) < 0.05. Organizational communication has a positive and significant effect on the performances of employees BUMDes Parringan Madu Parungan Madu BUMDes with a t-value of 2.662 with a p-value (0.012) <0.05. Organizational commitment and organizational communication affect the performance employees of BUMDes Parringan Madu simultaneously with a p value (0.000) <0.05. Keywords: organizational performance commitment, organizational communication,